2021
DOI: 10.3390/bios11090336
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Electrochemical Biosensors: Applications, Challenges, and Future Scope

Abstract: The electrochemical biosensors are a class of biosensors which convert biological information such as analyte concentration that is a biological recognition element (biochemical receptor) into current or voltage. Electrochemical biosensors depict propitious diagnostic technology which can detect biomarkers in body fluids such as sweat, blood, feces, or urine. Combinations of suitable immobilization techniques with effective transducers give rise to an efficient biosensor. They have been employed in the food in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
117
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(153 citation statements)
references
References 169 publications
0
117
0
Order By: Relevance
“…Electrochemical nanobiosensors are devices designed as alternatives to conventional laboratory-based detection techniques for disease diagnosis due to their robustness, small size, user-friendly operation, amenability for miniaturization, and potential for personalized diagnosis [4][5][6]. Electrochemical nanobiosensors comprise electroactive transducer platforms that anchor specific and selective bioreceptors, generating a nanobioconjugate.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical nanobiosensors are devices designed as alternatives to conventional laboratory-based detection techniques for disease diagnosis due to their robustness, small size, user-friendly operation, amenability for miniaturization, and potential for personalized diagnosis [4][5][6]. Electrochemical nanobiosensors comprise electroactive transducer platforms that anchor specific and selective bioreceptors, generating a nanobioconjugate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, knowing the concentration of L-Tyr in a pharmaceutical product can provide accurate information about the bioavailability of the drug in the body and the amount of active substance in relation to the rate at which it is absorbed into the body. The essence of a biosensor is to convert the biological response into an electrical signal, and to manufacture it, materials such as enzymes, antibodies, and nucleic acids are used, which requires multidisciplinary research in chemistry, medicine, pharmacy, biology, and engineering [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hassoun et al [ 7 ] proposed an SVM-based classification model to classify three cell types. Singh et al [ 8 ] reviewed recent advancements in electrochemical biosensors and the application of machine learning in these biosensing applications including the SERS biosensors. In addition, some of the recent studies have also demonstrated successful biosensing applications in response to the COVID-19 pandemic, such as in the detection of SARS-CoV-2 related proteins or in the detection of the virus itself [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%